KEANEKARAGAMAN MALVACEAE DI PEKARANGAN YANG DIMANFAATKAN OLEH MASYARAKAT DI DUSUN TELAGA SEGOAR, DESA LOLOAN, KECAMATAN BAYAN, KABUPATEN LOMBOK UTARA - Nutrinem; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
This study aims to determine the utilization of Malvaceae growing in the yards of people in Telaga Segoar Hamlet, Loloan Village, Bayan District, North Lombok Regency. Based on observations, there are two species of Malvaceae, namely: Theobroma cacao and Ceiba pentandra. T. cacao seeds are sold as raw materials for the chocolate industry. C. pentandra fruit fiber is used to fill mattresses, pillows, and bolsters.